Model of Students' Prophetic Character Building of Madrasah Aliyah in Responding to Global Sociocultural Change Era - M Arief Affandi; Nur Ali; Ahmad Barizi (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aims to uncover and formulate a conceptual model, implementation strategy, and impact assessment of building prophetic character in students to address sociocultural changes in the global era. Using a qualitative multi-case study design, research was conducted at Madrasah Aliyah Swasta (MAS) Al-Ittifaqiah 2 Ogan Ilir and Madrasah Aliyah Negeri (MAN) 3 Palembang. Data were collected through observations, interviews, and documentation. Findings reveal that the vision is based on four pillars—the Qur'an and Hadith, culture, Pancasila, and government—while addressing consumer needs and anticipating sociocultural changes. This vision incorporates values of humanization, liberation, and transcendence, aiming to create "Ulama-intellectuals and intellectuals-Ulama." The model is executed through four pathways: formal education (KBM PAI) to establish an understanding of prophetic values, school-boarding culture to practice these values habitually and build discipline, extracurricular activities to stimulate the internal application of prophetic values, and family and environment to provide external control and reinforcement. Internal and external sociocultural factors act as both supporting and inhibiting instruments. The program fosters individual and social transformation, increasing participation in religious, environmental, and social activities. It also enhances the Madrasah's image as a holistic institution, addresses sociocultural anomalies, and promotes the prophetic paradigm, resulting in a resilient and adaptable prophetic character framework suitable for the global era. The study introduces the Interconnected-Prophetic Elaboration to Sociocultural Change (I-PESC) model, which effectively builds prophetic character, balancing spiritual and social dimensions while promoting unity and moderation. Future research should incorporate field studies to validate these findings and provide more robust evidence.